Crossing Through The Information Barrier - mutiara, mutiara; Iskandar, Budi Permadi (Journal of Business and Management, 2012)
In the present times, the advance technology has made media become accessible for almost everyone and eventually the excessive information makes people barricade themselves, including from marketing messages. As one of the world leading advertising agencies, Dentsu Inc. developed Cross Communication approach to create marketing strategy based on AISAS model. DentsuÃ¢â‚¬â„¢s Cross Communication marketing approach is designed to reach in through customer barrier and enticing them out from the solitary. Using the scenario idea and contact points, Cross Communication strategy delivers the message to consumers more efficient than the conventional Integrated Marketing Communication. Ã‚Â Key Words: Marketing, Dentsu, The Dentsu Way, Cross Communication, StrategyÃ‚Â